Heat Shock Protein–Peptide and HSP-Based Immunotherapies for the Treatment of Cancer - Shevtsov, Maxim; Multhoff, Gabriele (Frontiers in Immunology, 2016)
Intracellular residing heat shock proteins (HSPs) with a molecular weight of approximately 70 and 90 kDa function as molecular chaperones that assist folding/unfolding and transport of proteins across membranes and prevent protein aggregation after environmental stress. In contrast to normal cells, tumor cells have higher cytosolic HSP70 and Hsp90 levels which contribute to tumor cell propagation, metastasis and protection against apoptosis. In addition to their intracellular chaperoning functions, extracellular localized and membrane-bound HSPs have been found to play key roles in eliciting anti-tumor immune responses either by acting as carriers for tumor-derived, immunogenic peptides, as adjuvants for antigen presentation or as targets for the innate immune system. The interaction of HSP-peptide complexes or peptide-free HSPs with receptors on antigen presenting cells (APCs) promotes the maturation of dendritic cells (DCs), results in an up-regulation of MHC class I and class II molecules, induces secretion of pro- and anti-inflammatory cytokines, chemokines, and immune modulatory nitric oxides and thus integrate adaptive and innate immune phenomena. Herein, we aim to recapitulate the history and current status of HSP-based immunotherapies and vaccination strategies in the treatment of cancer.